2013
DOI: 10.1007/s13277-013-1185-1
|View full text |Cite
|
Sign up to set email alerts
|

Significance and prognostic value of Gli-1 and Snail/E-cadherin expression in progressive gastric cancer

Abstract: Abnormal activation of the hedgehog (Hh) signaling pathway has been found to be involved in the occurrence, invasion, and metastasis of cancers. Epithelial-mesenchymal transition (EMT) also plays an important role in the invasion and metastasis of cancers. However, the significance of the Hh signaling pathway and EMT in the invasion and metastasis of gastric cancer is still unclear. This study aimed to investigate the significance and prognostic value of the Hh signaling pathway and EMT in progressive gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…Gli1 has been identified as the final transcriptional effector and the key marker of the Hh signaling pathway, and has been shown to be activated in various human malignancies such as prostate cancer and gastrointestinal cancer [30, 31]. Additionally, a previous study showed that, in GC, the levels of the Hh pathway marker Gli1 were associated with levels of the EMT markers E-cadherin and snail [32]. Interestingly, a recent study by Wang et al suggested that Gal-1 is required for Hh signaling pathway activation in pancreatic cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…Gli1 has been identified as the final transcriptional effector and the key marker of the Hh signaling pathway, and has been shown to be activated in various human malignancies such as prostate cancer and gastrointestinal cancer [30, 31]. Additionally, a previous study showed that, in GC, the levels of the Hh pathway marker Gli1 were associated with levels of the EMT markers E-cadherin and snail [32]. Interestingly, a recent study by Wang et al suggested that Gal-1 is required for Hh signaling pathway activation in pancreatic cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…Out of several Hh target genes, Gli-1 is a major transcription factor of the Hh signaling pathway (6). High expression of Gli-1 has been reported in several cancers, including gastric and colon cancer, in contrast to normal cells (6,23). Wang et al (23) reported that Gli-1 expression increased markedly in progressive gastric cancer and was closely associated with increased Snail (EMT marker) expression and decreased E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of Gli-1 has been reported in several cancers, including gastric and colon cancer, in contrast to normal cells (6,23). Wang et al (23) reported that Gli-1 expression increased markedly in progressive gastric cancer and was closely associated with increased Snail (EMT marker) expression and decreased E-cadherin expression. The positive Gli-1 expression group had a significantly increased invasion depth and a higher percentage of patients with lymph node (LN) invasion compared with the negative Gli-1 expression group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations